Seismic Vulnerability and Rehabilitation Strategies for Industrial RC Structures - Hosen, Kamal (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The catastrophic impact of building collapses or severe structural damage during significant earthquakes has led to considerable economic losses, serious injuries, and tragic loss of life. Retrofitting has emerged as a globally recognized solution, particularly for critical structures such as historical buildings and aging constructions that have experienced degradation over time. Unlike traditional repair and rehabilitation methods, retrofitting offers a more effective and practical approach, markedly enhancing the strength, resilience, and overall lifespan of structures.
Keywords: seismic retrofitting; seismic assessment; steel bracing; concrete jacketing; structural vulnerabilities